2014
DOI: 10.1007/s12161-014-9883-x
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Methods Applied to Assess the Effects of Gamma Irradiation on Color, Chemical Composition and Antioxidant Activity of Ginkgo biloba L

Abstract: The extracts from the leaves of Ginkgo biloba are widely used in medicines and food supplements in order to overcome different health problems. To provide decontamination, irradiation is a safe and effective technique, particularly suitable to be integrated in quality control of the postharvest samples. In this study, different analytical methods were applied to assess the effects of gamma irradiation (1 and 10 kGy) in G. biloba color, chemical composition and antioxidant properties. Irradiation preserved macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…The alterations induced by the gamma-irradiation in dry herbs and spices are related with the radiation dose applied, and generally, result in an increase of the total phenolic compound contents [104], whereas by using gamma-irradiation at 10 kGy, in Thymus vulgaris L., no modification in the phenolic profile and bioactive properties, were observed [105]. On the other hand, the gamma-irradiation can either decrease or improve the bioactivity of irradiated samples, depending on the changes in the structure of different antioxidant molecules and/or breaking some chemical bonds [106]. The influence of different radiation doses (1, 5, and 8 kGy) were also verified on the color, organic acids, total phenolics, total flavonoids, and antioxidant activity of dwarf mallow (Malva neglecta Wallr.)…”
Section: Sanitizing Methodsmentioning
confidence: 99%
“…The alterations induced by the gamma-irradiation in dry herbs and spices are related with the radiation dose applied, and generally, result in an increase of the total phenolic compound contents [104], whereas by using gamma-irradiation at 10 kGy, in Thymus vulgaris L., no modification in the phenolic profile and bioactive properties, were observed [105]. On the other hand, the gamma-irradiation can either decrease or improve the bioactivity of irradiated samples, depending on the changes in the structure of different antioxidant molecules and/or breaking some chemical bonds [106]. The influence of different radiation doses (1, 5, and 8 kGy) were also verified on the color, organic acids, total phenolics, total flavonoids, and antioxidant activity of dwarf mallow (Malva neglecta Wallr.)…”
Section: Sanitizing Methodsmentioning
confidence: 99%
“…During irradiation process, the dose was estimated using Amber Perspex routine dosimeters (batch V, from Harwell Company, U.K.), following the procedure previously described by Pereira et al (2015). The estimated doses, dose rates and dose uniformity ratios (D max /D min ) were, respectively: 1.20 ± 0.07 kGy, 2.57 ± 0.15 kGy h −1 , 1.20 for sample 1 and 8.93 ± 0.14 kGy, 1.91 ± 0.03 kGy h −1 , 1.02 for sample 2.…”
Section: Methodsmentioning
confidence: 99%
“…The use of irradiation has been increasingly accepted for decontamination and conservation, since it does not significantly affect (at specific doses) the organoleptic and physico-chemical properties of the irradiated matrices (Alothman et al, 2009;Kirkin et al, 2014), including G. biloba (Pereira et al, 2015). This method reduces reliance on chemical fumigants (ethylene oxide and methyl bromide), which have been pointed out as mutagens and carcinogens to humans, leave chemical residue on plants and destroy the ozone layer in the atmosphere (Migdal and Owczarczyk, 1998;Chmielewski and Migdał, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Etyemez [55] and Pereira et al [56] found that fatty acids were not affected by the irradiation process and that there was no significant difference between the irradiated and non-irradiated control samples [57].…”
Section: Linoleic Acidmentioning
confidence: 99%
“…Stefanova et al found that the gamma irradiation doses of 7.5 kGy, 10 kGy, and 15 kGy resulted in a decrease in PUFAs and that the amount of linolenic acid decreased due to the increase in the dose of irradiation [40]. Chen et al [39,55,56] indicate that the effect of irradiation on linolenic acid in their studies is not significant. Statistically, it was determined that the storage period was effective at the level of p<0.05 on the amount of linolenic acid.…”
Section: Linolenic Acidmentioning
confidence: 99%